Impact of External Labor Migration on Labor Market Development - SEREDINA, Maryia Igorevna; TRETJAKOVA, Galina Viktorovna; OBEREMKO, Tatyana Viktorovna; KOZHINA, Veronika Olegovna; LEBEDEV, Kostyantyn Anatolevich (Journal of Advanced Research in Law and Economics, 2017)
It has been established that modern labor migration is one of the most complex subsystems of international economic relations that impacts the world economy in a certain way and is a top priority for many scientists around the globe. It has been proven that migration policy along with other socio-economic development institutions affect and dictate the development of human resources, and therefore each country has a certain HR management style. It has been determined that lower labor market tension is promoted by creating new jobs by former migrant workers using money earned abroad. To assess the impact of labor migration on the development of labor market, a methodology used for estimating the impact of external labor migration on labor market development has been developed. By using this approach, it has been found out that the hypothetical unemployment rate is above the actual recorded rate.